AB0645 CANNABINOIDS IN THE TREATMENT OF PAIN RELATED TO SYSTEMIC SCLEROSIS SKIN ULCERS: OUR EXPERIENCE. (June 2019) - Cocchiara, Emanuele; Spinella, Amelia; Magnani, Luca; Lumetti, Federica; Palermo, Adalgisa; Baiocchi, Gianluigi; Salvarani, Carlo; Giuggioli, Dilia
Abstract : Background: Skin ulcers (SU) represent one of the most frequent complications of Systemic Sclerosis (SSc), characterized by severe chronic pain and frequent complications. Pain related to SSc SU(SSU) remains yet an area of significant unmet need. Moreover, pain control is fundamental for the wound care procedures in SSc patients (pt), increasing treatment adherence and compliance to skin ulcers dressing changes. The pain relief provided by standard therapy (i.e. NSAIDs, tramadol) is often inadequate or dose limited by side effects. Opioids currently are the mainstay of SSU pain treatment but burdened by side effect profile and/or ineffective. Thus, novel analgesic strategies need to be investigated. Cannabidiol (CBD), one of many constituents of the Cannabis sativa, has received renewed interest in the treatment of numerous pathological conditions. Objectives: Evaluate our experience to define the efficacy of CBD preparation in patients with SSU. Methods: 25 SSc pt (F/M 22/3, mean age 52.3 ± 12.9-SD-years), referred to our Scleroderma Unit during 2018, were consecutively included. In all pt the disease was complicated by long-standing, painful SU resistant to opioids. Pain was classified as severe, according to WHO guidelines in all subjects. 25/25 pt carried out systemic (calcium-channel blockers, prostanoids and/or anti-ET receptors) and local (debridement and dressing) therapies. The CBD (10% oral administration oil) was used daily for the treatment of SSU-related pain. We performed both an oral (five drops bid) as local treatment (two drops in the site of SSU) during surgical debridement of SSU for a period of 5.9 ± 3.2 SD months. Patients have been provided with a diary to record the following symptoms daily: self-evaluation of pain at the same time in the evening, using a visual analog scale (VAS), use of other analgesics, eventual side effects. Health assessment Questionnaire-Disability index (HAQ-DI) was administrated baseline and at the end of treatment. Safety of CBD was evaluated by patient's records of side effects, while vital signs and laboratory parameter variations were monitored at each weekly medication. Results: The local treatment with CBD produced a significant reduction of SSU-related pain. After 1 month of therapy, pain VAS decreased from 94.8 ± 8.72 SD to 54.7 ± 9.4 SD (P<0.0001), total hours of sleep increased from 2.56 ±1.28 SD to 5.67 ± 0.85 SD (P <0.000). Additional analgesic therapy was necessary in 12/25 (48%). After 2 months, further clinical improvement was observed: the pain VAS reduced to 40.9 ± 12.9 SD, the mean total hours of sleep per night was 6.10 ± 0.85 SD and the HAQ-DI decreased from 1.1 ± 0.67 SD (baseline) to 0.46 ± 0.46 SD at the last patients' evaluation, when complete healing of SSU and pain relief were obtained and CBD was discontinued. 20/25 (80%) pt registered a better compliance to the local wound management. No reported significant side effects with CBD oil. Conclusion: Our study suggests that the use of CBD as a local therapy is effective and safe in maintaining analgesia in patients with SSU; not secondarily it could be essential for an adequate healing of a local wound with consequent improvement of SSc patients' quality of life and compliance on local SSU management. Further larger-scale studies will be needed to finally demonstrate CBD efficacy and to monitor long-term effects. Disclosure of interests: None declared